Hydronium 4-oxo-1,4-dihydropyridine-3-sulfonate dihydrate - Zhi-Biao Zhu; Shan Gao; Seik Weng Ng (Acta Crystallographica Section E, 2009)
2-Hydroxypyridine when treated with concentrated sulfuric acid is sulfonated at the 3-position to yield the title hydrated salt, H3O+·C5H4NO3S−·2H2O. In the crystal structure, the cations, anions and uncoordinated water molecules are linked by extensive O—H...O and N—H...O hydrogen bonds into a three-dimensional network. The crystal studied is a non-merohedral twin with a twin component of 36%.